2022
DOI: 10.34117/bjdv8n6-067
|View full text |Cite
|
Sign up to set email alerts
|

Patologias no concreto armado em elementos de projetos estruturais: uma revisão / Pathologies in reinforced concrete in elements of structural projects: a review

Abstract: Embora os avanços tecnológicos na área da engenharia civil tenham avançado , muitas estruturas apresentam um desempenho não satisfatório, devido a erros de projeto, má qualidade dos materiais, falta de manutenção e dentre muitos outros fatores que contribuem para a degradação da estrutura. Portanto, o presente estudo apresenta as patologias no concreto armado que ocorrem nos principais grandes elementos de projeto estrutural como as fundações, as lajes, as vigas e os pilares.  Geralmente as manifestações patol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…That is, as evaluated in the present study, they are endogenous causes, which if they had met the minimum requirements given in regulations, they would have been avoided. Silva (2022) still proposes in his study that the most recurrent manifestations are due to the absence of structural elements, such as beams and pillars; which is confirmed in this study.…”
Section: Incidence Analysis Of the Variation Of Types Of Crackssupporting
confidence: 82%
See 1 more Smart Citation
“…That is, as evaluated in the present study, they are endogenous causes, which if they had met the minimum requirements given in regulations, they would have been avoided. Silva (2022) still proposes in his study that the most recurrent manifestations are due to the absence of structural elements, such as beams and pillars; which is confirmed in this study.…”
Section: Incidence Analysis Of the Variation Of Types Of Crackssupporting
confidence: 82%
“…As in the study carried out by Lourenço (2022), it was observed that the constructive system that presents the highest occurrence of cracks was in masonry with 50% of the total observed. Marcolino et al (2019), Bento et al (2021 and Silva (2022), emphasize the need for projects and details, making the lack a failure for the emergence of pathological manifestations. That is, as evaluated in the present study, they are endogenous causes, which if they had met the minimum requirements given in regulations, they would have been avoided.…”
Section: Incidence Analysis Of the Variation Of Types Of Cracksmentioning
confidence: 99%